Latent Structure of Combined Autistic and ADHD Symptoms in Clinical and General Population Samples: A Scoping Review - Krakowski, Aneta D.; Szatmari, Peter; Crosbie, Jennifer; Schachar, Russell; Duku, Eric; Georgiades, Stelios; Anagnostou, Evdokia (Frontiers in Psychiatry, 2021)
Background: Many phenotypic studies have estimated the degree of comorbidity between Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD), but few have examined the latent, or unobserved, structure of combined ASD and ADHD symptoms. This is an important perquisite toward better understanding the overlap between ASD and ADHD. Methods: We conducted a scoping review of studies that examined the factor or latent class structure of ASD and ADHD symptoms within the same clinical or general population sample. Results: Eight studies met final inclusion criteria. Four factor analysis studies found that ASD and ADHD domains loaded separately and one found that some ASD and ADHD domains loaded together. In the three latent class studies, there were evidence of profiles with high levels of co-occurring ASD and ADHD symptoms. Conclusions: Our scoping review provides some evidence of phenotypic overlap between ASD and ADHD at the latent, or unobserved, level, particularly when using a “person-centered” (latent class analysis) vs. a “variable-centered” (factor analysis) approach.